Incidence of Adverse Drug Reactions (ADRs) and their Determinants among Sputum-Positive Pulmonary TB Patients in A Metropolitan Area, Bengaluru: A Prospective Study - Divakar, Manasa; Ananth Ram; Lalitha K (National Journal of Community Medicine, 2023)
Background: India accounts for 2.42 million new Tuberculosis cases in 2022. Treatment adherence is major challenge, ADRs being one of the main causes of poor adherence. Early identification and addressing of ADRs can improve adherence, reducing associated morbidity and drug resistance. With introduction of daily FDC regimen in India, we intend to study incidence of ADRs and their determinants among Pulmonary TB patients who are on FDC daily regimen. Methodology: Newly diagnosed drug-sensitive PTB patients aged 18 years and above were recruited. A pretested questionnaire was administered and patients were followed up to document ADRs. Causality and severity were assessed using the WHO-UMC scale and Hartwig’s severity assessment scale respectively. Results: Among the study participants’, 95 (78.5%) developed any ADRs. Incidence rate was 13.2 (6.98–19.22) per 100-person month follow-up with GI symptoms being most common. Increasing age [OR=4.7(1.6–14.8)] and weight [OR=5.1(1.3–16.2)] were found to be significantly associated with ADRs. All ADRs were classified as ‘probable’ and ‘mild’ in nature according to WHO scale and Hartwig’s severity assessment scale respectively. Conclusion: Occurrence of ADRs is common, most of them are mild, and occurring in intensive phase. Hence, early identification and appropriate counselling during intensive phase is critical.